A low-offset low-quiescent nanometer CMOS power amplifier for portable applications - Xiao, Fei (2014)
With the increasing demand for the portable devices, the performance of each component in the portable devices becomes more and more critical. Since headphone amplifier is one of the most important components of the portable headphone, a lot of works have been done on the design of the headphone amplifier. Quiescent power and distortion are the most significant parameters which describe the performance of the headphone amplifier. Due to its high efficiency and low quiescent power performance, class G amplifier is one of the most common headphone amplifiers. However, the linearity and the overall distortion of the class G amplifier will not be quite good due to its switching structure.